1989
DOI: 10.1007/bf00269051
|View full text |Cite
|
Sign up to set email alerts
|

Sequential release of both basic and acidic isoperoxidases to the media of suspension cultured cells of Capsicum annuum

Abstract: The establishment of suspension cell cultures from trimmed cotyledons of pepper (Capsicum annuum L.) provides a new experimental system for studying the relationship between release of peroxidase (EC 1.11.1.7) into the free intercellular spaces and plant cell growth. In contrast with several other species, the total peroxidase activity in the medium increased continuously during the post-exponential growth phase of the pepper cell culture, and this was correlated with the growth inhibition of pepper cells cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…As was the case for the grapevine peroxidase isoenzyme group BPrx Hpl, lupin peroxidase isoenzyme group BPrx Hpl was recovered with a yield of 93% in the vacuole fraction (Table II). Similar results (Table II) were found in Capsicum annuum (7,8), lettuce (Lactuca sativa) (9) and catharanthus (Catharanthus roseus) (10).…”
Section: The Bprx Hpl Isoenzyme Group: a Distinctive Peroxidase Isoensupporting
confidence: 89%
“…As was the case for the grapevine peroxidase isoenzyme group BPrx Hpl, lupin peroxidase isoenzyme group BPrx Hpl was recovered with a yield of 93% in the vacuole fraction (Table II). Similar results (Table II) were found in Capsicum annuum (7,8), lettuce (Lactuca sativa) (9) and catharanthus (Catharanthus roseus) (10).…”
Section: The Bprx Hpl Isoenzyme Group: a Distinctive Peroxidase Isoensupporting
confidence: 89%
“…2). A similar variation in the level of extracellular peroxidase activity has been found for suspension cell cultures of Capsicum annuum (Cuenca et al 1989) and Gamay grapevine cultures (Garcia-Florenciano et al 1991).…”
Section: Resultssupporting
confidence: 71%
“…In at least four species under different treatments, we have established correlations between growth limitation, lignin accumulation, and increase of total peroxidase activity and ethylene emission (Table 1). It was found that during growth responses to several stimuli, peroxidase varied in a two-step manner, with an early variation of cationic (basic) isoperoxidases preceding changes in anionic (acidic) ones (Boyer et al, 1983;Gaspar et al, 1985a;Cuenca et al, 1989). Because there were arguments to involve basic and acidic peroxidases in auxin catabolism, in ethylene production, and in lignin polymerization, respectively, a general scheme involving sequential events, including changes in IAA level, ethylene production, and growth limitation through lignin-induced wall rigidification, was drawn ( Fig.…”
Section: Sequential Intervention Of Different Hormones In Growth Procmentioning
confidence: 99%